Utilization of Antenatal Care (ANC) Services by Pregnant Women in Binjai City and Factors Affecting (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Antenatal care services have an influence on fetal growth or during pregnancy, one effort to reduce maternal mortality due to complications is through the use of antenatal care. Based on data from the Health Profile of Kebun Lada Public Health Center, it is known that the scope of ANC services (K1 and K4) in 2017 is K1 96% AND K4 84%. In 2018 that is K1 82.7% and K4 81%. Where there is a difference in the percentage of coverage of K1 and K4 visits. The research was an analytical survey using Cross Sectional with a sample of 76 people. This research uses chi-square data analysis method with accidental sampling technique to find out the significant influence between, Knowledge, Attitude, ANC Service Facilities, Husband / Family Support and Health Staff Support. This research shows there is influence of Knowledge (p = 0,000), Attitude (p = 0,000), Service Facilities (p = 0,000), Husband / family Support (p = 0,000), Officer Support with (p = 0,001) with Utilization of Antenatal Care Services where p-value 0.05. This study, showed that all factors affect the Antenatal Care service. Health workers, especially midwives, are expected to maintain health education and promotion and motivation on a regular basis about the importance of regular antenatal care.